Development and Operation of the Dalian Cruise Port in China. (16th February 2022) - Gong, Lina
Abstract : China's cruise industry has developed rapidly in the past ten years, and China's cruise port construction has flourished. A total of 20 cities along the coast of mainland China have built or planned to build cruise terminals. According to WTO estimates, China will gradually become the world's largest source country of cruise passengers and cruise travel consumers in the future. Due to different national conditions, the business model and development prospects of Chinese cruise ports are different from those of foreign ports. It requires finding the pioneers of domestic cruise ports to take the lead, providing advice on the development and operation of cruise ports. Dalian Cruise Port is actively formulating its cruise industry development plan, expanding the cruise port, and improving the supporting facilities in the cruise port area. Based on the characteristics of the operation of the Dalian cruise port, we use the gray model to make a vague prediction of the future development of the cruise port. It reflects the advanced operation mode of Dalian Port. This research systematically analyzed cruise port operations and maritime cruise transportation. Because the cruise port's business model and prospects are essential to the cruise port industry, China's cruise ports must learn more advanced operating models.